2017
DOI: 10.1021/acsomega.7b00420
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Scope of Electron-Deficient C–H Building Blocks: Direct Arylation of Pyromellitic Acid Diimide

Abstract: Direct C–H activation of pyromellitic diimide (PMDI) is reported for the first time. The method avoids cumbersome pathways involving bromination usually required for further cross-coupling. Good to excellent yields of mono- and di-substituted PMDI derivatives can be obtained under optimized reaction conditions. The reaction scope was also explored, and the materials were characterized with respect to their thermal, optical, and electronic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…[17] According to recent studies, am ore stable Buchwald catalyst generation three (Pd 2 G 3 )w as found to be ag ood alternative to Pd 2 (dba) 3 in DA. [18,19] Indeed, as imilar result was observed with Pd 2 G 3 ( Table 1, entry 6). We thus used Pd 2 G 3 as catalysti na ll followinge ntries for the sake of abetter reproducibility.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…[17] According to recent studies, am ore stable Buchwald catalyst generation three (Pd 2 G 3 )w as found to be ag ood alternative to Pd 2 (dba) 3 in DA. [18,19] Indeed, as imilar result was observed with Pd 2 G 3 ( Table 1, entry 6). We thus used Pd 2 G 3 as catalysti na ll followinge ntries for the sake of abetter reproducibility.…”
supporting
confidence: 76%
“…It is important to note that we here used commercial and stored Pd 2 (dba) 3 , which is known to generate Pd nanoparticles during storage and thus potentially affect reaction reproducibility . According to recent studies, a more stable Buchwald catalyst generation three (Pd 2 G 3 ) was found to be a good alternative to Pd 2 (dba) 3 in DA . Indeed, a similar result was observed with Pd 2 G 3 (Table , entry 6).…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…This method has gained considerable recent momentum as a significantly environmentally and economically attractive alternative to classical cross-coupling such as Suzuki-Miyaura, Negishi, and Stille reactions [6][7][8][9][10]. With fewer steps and accessible reagents, complex organic molecules are nowadays easily accessible with C-H activation [11][12][13][14][15][16][17][18][19][20]. Nevertheless, this reaction usually requires high temperatures and organic solvents to achieve new C(sp 2 )-C(sp 2 ) bonds [21].…”
Section: Introductionmentioning
confidence: 99%
“… 15 18 The smallest of aromatic diimides, pyromellitic diimide (PMDI), has received significantly less attention in these areas than the larger naphthalene and perylene diimides despite exhibiting promising behavior in electronic settings 14 , 19 alongside interesting absorption and emission characteristics. 9 , 20 Explanations for this disparity often point to the challenge of incorporating functionalities at the PMDI core positions 21 and the more negative voltages required by PMDI-based redox systems to reach their reduced states. 11 , 22 With these perceived limitations in mind, we sought to demonstrate a molecular design that leads to significant shifts of PMDI reduction potentials toward more positive voltages.…”
Section: Introductionmentioning
confidence: 99%